Students’ Interest in Learning English Online at SMA Negeri 3 Tualang during Covid-19 Pandemic - Fitri Rahayu; Dinovia Fannil Kher (Universitas Negeri Padang, 2022)
This study aims to know how students' interest in learning English online in SMA Negeri 3 Tualang During Covid-19 Pandemic. The sample of this study was the eleventh-grade students of SMA Negeri 3 Tualang. The sample was carried out using a proportionate sampling method. The number of samples in this study was 160 students. Data were collected utilizing a questionnaire and strengthened by interviews. This research is descriptive research with a quantitative approach. Some of the applications used by students and teachers during online learning are WhatsApp, Telegram, Google Classroom, and Zoom. Interest in learning is one of the essential things in the smooth learning process, both face to face and online. External and internal factors also influence students' interest in learning English online. This study indicates that students' interest in learning English online is in the medium category, with the average value of each indicator being; feeling pleasure was 2,966, Students engagement was 2,978, and students involvement was 3,056. The overall average is 3,000 or is in the medium category.